Reinfection Rate after Successful Helicobacter pylori Eradication in Children - Najafi, Mehri (Tehran University of Medical Sciences, 2010)
OBJECTIVE: Reinfection rate of Helicobacter pylori after successful eradication is low in developed countries. This study was performed to determine the reinfection rate of H. pylori during a follow up period of 12 months in Iranian children. METHODS: In this prospective study, children with H. pylori infection were treated with triple omeprazole based regimen. Patients with negative (13)C urea breath test (UBT) performed after 8 weeks of therapy, were followed up by the same test after 1 year. FINDINGS: Thirty seven patients, aged 5 to 17 years, were studied. Among them 25 (67.5%) were boys. After eradication therapy of H. pylori, 34 patients had negative (13)C UBT. Reinfection occurred in 5 (14.7%) patients. Reappearance or continuing symptoms after treatment were associated with higher rate of recurrence (P=0.042). CONCLUSION: Recurrence rate of H. pylori was high in our children. Successful eradication significantly decreased complaints and further symptoms. Follow up and reevaluation of patients is necessary especially when there are symptoms after eradication.